Effects of Continuous Positive Airway Pressure on Nonalcoholic Fatty Liver Disease in Patients with Obstructive Sleep Apnea: A Systematic Review - Tamin, Susyana; Ardiantara, Sabda; Rudiatmoko, Diar Riyanti (The Indonesian Society for Digestive Endoscopy, 2023)
Background: Nonalcoholic fatty liver disease (NAFLD) is associated with obstructive sleep apnea (OSA). Continuous positive airway pressure (CPAP) is the first-line therapy for OSA. However, the effect of CPAP on NAFLD in patients with concomitant OSA is still unclear. This study aims to identify the use of CPAP on NAFLD in patients with OSA. Method: A systematic literature search was performed using particular keywords and medical subheadings in three journal databases: Cochrane, PubMed, and EBSCOhost. The results were screened and assessed using inclusion and exclusion criteria by three independent authors. The Randomized controlled trial (RCT) quality was evaluated with Jadad scale and the cohort studies quality was assessed with Newcastle-Ottawa quality assessment scale.Results: Two RCTs and three cohort studies were eligible to fulfil the inclusion criteria, consisting of 620 total patients. Two RCTs showed no statistically significant improvement after CPAP treatment in NAFLD based on intrahepatic triglyceride (measured by proton magnetic resonance spectroscopy), liver stiffness measurement, serum cytokeratin-18 fragment, and liver function blood test parameters. Meanwhile, 2 cohort studies in adults and 1 cohort study in children showed significant improvement in ALT, AST, and APRI. However, one cohort study showed no significant improvement in serum fibrosis markers and transient elastography measurement after CPAP treatment.Conclusion: CPAP might be beneficial in some patients with OSA to improve NAFLD, but further research that includes many subjects and longer duration of CPAP therapy is needed to confirm this result.